Bringing the Concept of Climate-Smart Agriculture to Life : Insights from CSA Country Profiles Across Africa, Asia, and Latin America - Sova, Chase Anthony; Grosjean, Godefroy; Baedeker, Tobias; Nguyen, Tam Ninh; Wallner, Martin; Nowak, Andreea; Corner-Dolloff, Caitlin; Girvetz, Evan; Laderach, Peter; Lizarazo, Miguel (World Bank, and the International Centre for Tropical Agriculture, Washington, DC, 2018)
Bringing the Concept of Climate-Smart Agriculture to Life: Insights from CSA Country Profiles across Africa, Asia, and Latin America The Climate-Smart Agriculture (CSA) Country Profile Series assesses climate change challenges and solutions in the agricultural sectors of more than 30 countries across Africa, Asia, and Latin America and the Caribbean (LAC). This report introduces the first analysis of a new dataset drawn from these profiles, aggregating bottom-up results from individual expert assessments of CSA technologies. It offers the most complete overview to date of technologies considered climate-smart around the world. The emerging insights shed light on technologies in different locations and farming systems, their strengths and weaknesses across different dimensions of climate-smartness, and their specific barriers to adoption. As a result, a more concrete and specific picture of CSA emerges that could help demystify the concept, reveal synergies between the three CSA pillars (productivity, adaptation, and mitigation), and allow for more targeted technology deployment and scale-up.